PENERAPAN MEDIA SLIDE UNTUK PENINGKATAN HASIL BELAJAR PADA MATA PELAJARAN PPKn KELAS V - Gusrianti Gusrianti (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
Classroom action research has been carried out at SDN 105/X Rantau Makmur with the aim of improving student learning outcomes in PPKn through the use of Slide media. Education so far has been carried out conventionally, this causes educational outcomes not to be optimally in line with expectations. This class action research was carried out in 2 cycles with 2 meetings in each cycle. Each meeting of the educational process using Slide media. As an instrument for collecting information, there are student worksheets, daily test sheets and observation sheets filled out by observers, with steps for planning action, implementing action, observing, assessing and reflecting for each cycle. Student learning outcomes have increased in all indicators from the first cycle to the second cycle. This change shows an increase in student learning activities. Each group shows an increase in value and the average individual score also increases. The use of slide media has a positive impact on students' activities and learning outcomes.